A methodological proposal of the Sustainolive international research project to drive Mediterranean olive ecosystems toward sustainability - De Luca, Anna Irene; Iofrida, Nathalie; González de Molina, Manuel; Spada, Emanuele; Domouso, Pablo; Falcone, Giacomo; Gulisano, Giovanni; García Ruiz, Roberto (Frontiers in Sustainable Food Systems, 2023)
Mediterranean olive growing is an excellent model of the multifunctionality of agriculture in the rural areas. It characterizes, identifies and can sustain the socio-economic viability of rural areas, not only through the production of primary products, but also through the management of renewable natural resources, and the conservation of landscape and biodiversity. However, high level of mechanization, monocultures, intensive farming techniques, and the use of synthetic pesticides and fertilizers are threatening the environment and affecting rural communities in turn. In the last years, the agroecological discourse emerged and evolved along the time from a pure environmental and social concern to a transdisciplinary science merging agronomy, ecology and socio-economic sciences. Then, it assumed the purpose of responding to socioeconomic and to environmental concerns, as a response to the globalised industrial food processing and to intensive agriculture. In this context, the international research project Sustainolive, guided by an international consortium of stakeholders from academia and from the productive sector, has the aim of promoting sustainability in the olive oil sector through the implementation and promotion of innovative and technological solutions based on agroecological concepts and on the effective and active exchange of knowledge among actors. Through an innovative, transdisciplinary and multi-actor approach, Sustainolive combines different types of knowledge (e.g., scientific, empirical, traditional), disciplines (ranging all the way from engineering to the humanities) and methodological approaches (e.g., Life Cycle Sustainability Assessment and Social Agrarian Metabolism) to provide practical solutions that address the complexity of the olive sector.